Determination of histamine using chemical sensor based on amperometric technique using screen-printed polyurethane electrode (SPPE) compared to HPLC equipped fluorescence detector - Muhammad Abdurrahman, Munir; Khairiah Haji, Badri; Lee, Yook Heng; Nurul, Kusumawardani; Rizal, Fauzi (AIP Publishing, 2022)
For a long time, the presence of histamine in foods related to food poisoning owing to inappropriate storage of food. Histamine is generally used as an indicator of food safety. This study used HPLC to analyze histamine which was very accurate yet time-consuming and used many organic solvents which are not good for the environment. Therefore, the purpose of this work is to develop a non-enzymatic electrochemical technique to detect histamine using screen– printed polyurethane electrode (SPPE) in phosphate buffer solution (PBS) at pH 7.5, SPPE showed a very low oxidation potential of histamine at +0.31 V (vs. Ag/AgCl) avoiding perturbations from other amines such as cadaverine, putrescine and aniline. The developed method offered a satisfactory selectivity, detection limit at 0.17 µmol·L−1 and linear range at 10−4 – 1 mmol·L−1 for histamine detection. In addition, the proposed method was successfully applied to detect histamine with concentrations at 0.01 and 0.1 mmol·L−1 in fish mackerel and canned fish with recovery values ranging from 94 and 103%, respectively. Amperometric detection of histamine in fish samples using screen-printed polyurethane electrode was applied and compared with HPLC and presented high promise to be applied as an inexpensive and effective tool for food safety surveillance.